Particleboards from second growth woods of roble (Nothofagus obliqua), raulí (N. alpina) and a hybrid of both - Poblete W., Hernán (Bosque (Valdivia), 1989)
Second growth thinning materials from stands of roble (Nothofagus obliqua), rauli (Nothofagus alpina) and hybrid of both was utilized for particleboard production. Board properties (Bending strength, MOR, Internal bond, Thickness swelling, water absorption) were related to wood properties (Specific gravity, extracts, pH-value). Results indicate that wood from Raulí stands produces the best particleboards.